2022
DOI: 10.24071/ijiet.v7i1.5139
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Factors and Levels of Students’ Autonomy in Language Learning

Abstract: Students’ autonomy is important in language learning since students’ autonomy is considered one of the elements in successful language learning. This study aimed to explore the students’ autonomy levels in language learning by considering the characteristics of autonomous students and the factors that affected students’ autonomy. As a mixed-method study, this study combined questionnaires and interviews as the instruments. The sample of this research was 34 students of XII MIPA 1 of SMA Negeri 2 Semarang. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…This finding aligns with research from several researchers (Jaya et al, 2022;Suchona & Shorna, 2019). There are several different reasons why students face difficulties in speaking, including: Pronunciation problem: for many students, difficulty pronouncing English words is a severe barrier because improper pronunciation can lead to uncertainty and misunderstanding between interlocutors (Octaviani et al, 2024). The second is a lack of vocabulary, which students may struggle to enhance their speaking ability without regular practice.…”
Section: B Students' Shortcomings In Speakingsupporting
confidence: 87%
“…This finding aligns with research from several researchers (Jaya et al, 2022;Suchona & Shorna, 2019). There are several different reasons why students face difficulties in speaking, including: Pronunciation problem: for many students, difficulty pronouncing English words is a severe barrier because improper pronunciation can lead to uncertainty and misunderstanding between interlocutors (Octaviani et al, 2024). The second is a lack of vocabulary, which students may struggle to enhance their speaking ability without regular practice.…”
Section: B Students' Shortcomings In Speakingsupporting
confidence: 87%
“…This study reported that factors like prior experience, the learning context in terms of exam-oriented assessment, and teacher-dependency (on the part of the learners) due to teachers' spoon-feeding tendency that was adversely mediating the realization of learner autonomy. Similarly, Wiranti & Widiyati (2023) investigated 34 Indonesian learners' perspectives to conceptualize the influence of contextual factors on learner autonomy. The study found that the assigned tasks and activities, teachers' roles, and the learning environment are the important influences that positively support learners' autonomous learning.…”
Section: Contextual Factors and Its Influencesmentioning
confidence: 99%